Population genetic tools for Gonipterus sp. n. 2 and its egg parasitoid Anaphes nitens - Coetzee, Martin Petrus Albertus (University of Pretoria, 2021)
Dissertation (MSc (Genetics))--University of Pretoria, 2021.